PENERAPAN PENDEKATAN PROBLEM POSING TERHADAP PENINGKATAN KEMAMPUAN PENALARAN MATEMATIK SISWA SMP - Sugandi, Asep Ikin (PRISMA, 2018)
The purpose of this research is to examine the comparison of improvement of students' mathematical reasoning ability among the learning using problem posing approach with the use of ordinary learning. The method used in this research is experimental method with random sampling of class. The population in this study is all students of class VII SMP Negeri that exist in the city of Cimahi, while the sample is selected two classes VII from one junior high school in Cimahi. Instruments in this study consisted of two sets of tests in the form of a description problem. A set of questions to measure Early Mathematical Ability (KAM) and sort students into high, medium and low category (KAM). One other question is to measure the initial and final abilities of the aspects of mathematical reasoning. The instrument has fulfilled a good question in terms of validity, reliability, distinguishing power, and difficulty index. Based on the results of data processing, it can be concluded that the improvement of students 'mathematical reasoning ability using problem solving approach is better than ordinary learning, increasing students' mathematical reasoning ability which is higher than KAM or low, but KAM mathematical reasoning is no better than KAM low, the next result there is interaction between learning approach with KAM to mathematical reasoning. From these interactions, it is found in high KAM that the improvement of students 'reasoning ability using learning approach of problem posing is better than ordinary learning, but in low KAM there is no difference in improving students' mathematical reasoning ability among the learning using problem posing approach with ordinary learning. Â Keywords: Reasoning, Problem Posing